2012
DOI: 10.1007/s13593-012-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Sesuvium portulacastrum, a plant for drought, salt stress, sand fixation, food and phytoremediation. A review

Abstract: International audienceSesuvium portulacastrum L. is a pioneer plant species, used for sand-dune fixation, desalination and phytoremediation along coastal regions. The plant tolerates abiotic constraints such as salinity, drought and toxic metals. S. portulacastrum is also used as a vegetable, fodder for domestic animals and as an ornamental plant. S. portulacastrum grows luxuriantly at 100–400 mM NaCl concentrations. It further grows at severe salinity of 1000 mM NaCl without any toxic symptoms on the leaves. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 108 publications
1
48
0
Order By: Relevance
“…Apart from salt tolerance, Sesuvium also exhibits high potential for accumulation of heavy metals. It has shown high accumulation of cadmium (350–700 μg g −1 dry matter), lead (3,400 μg g −1 DW), arsenic (155 μg g −1 DW; reviewed in Lokhande et al, ), nickel (1,050 μg g 1 DW; Fourati, Wali, Vogel‐Miku, Abdelly, & Ghnaya, ), and cesium (536.10 μg g −1 ; Nikalje, Srivastava, Nikam, & Suprasanna, ). Also, Sesuvium has shown potential application for degradation of textile dyes such as reactive green HE4B (Patil, Lokhande, Suprasanna, Bapat, & Jadhav, ) and Reactive green 19A‐reactive green HE4BD (Lokhande, Kudale, Nikalje, Desai, & Suprasanna, ).…”
Section: Halophyte Cultivation and Its Potential Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from salt tolerance, Sesuvium also exhibits high potential for accumulation of heavy metals. It has shown high accumulation of cadmium (350–700 μg g −1 dry matter), lead (3,400 μg g −1 DW), arsenic (155 μg g −1 DW; reviewed in Lokhande et al, ), nickel (1,050 μg g 1 DW; Fourati, Wali, Vogel‐Miku, Abdelly, & Ghnaya, ), and cesium (536.10 μg g −1 ; Nikalje, Srivastava, Nikam, & Suprasanna, ). Also, Sesuvium has shown potential application for degradation of textile dyes such as reactive green HE4B (Patil, Lokhande, Suprasanna, Bapat, & Jadhav, ) and Reactive green 19A‐reactive green HE4BD (Lokhande, Kudale, Nikalje, Desai, & Suprasanna, ).…”
Section: Halophyte Cultivation and Its Potential Applicationsmentioning
confidence: 99%
“…Essential oil extracted from leaves of Sesuvium has shown antibacterial, antifungal, and antioxidant activity (Magawa, Gundidza, Gweru, & Humphrey, ). Sesuvium is a rich source of amino acids, alkaloids, polysaccharides, saponins, minerals, steroids, and triterpines (reviewed in Lokhande et al, ).…”
Section: Halophyte Cultivation and Its Potential Applicationsmentioning
confidence: 99%
“…For example, Islam et al [56] reported that high level (100 mg•kg −1 ) As plus Cr caused a further decreased plant growth and chlorophyll content, increased MDA and H 2 O 2 contents as well as antioxidative enzymes activities significantly (P ≤ 0.05) and less severe inhibition of plant growth and oxidative damage was observed in O-795 (Cr-tolerant jute) than in O-9897 (Cr-sensitive jute) indicating variety O-795 had more efficient defense system to mitigate heavy metal induced oxidative stress. Some plants (such as Sesuvium portulacastrum L.) however posses the molecular and physiological flexibility [68] to deal with such parched sites. Also chelating agents like synthetic ethylenediamine tetra acetic acid (EDTA) was applied to Pb contaminated soil (total soil Pb 2500 mg•kg −1 ) and this increased the amount of bioavailable lead in the soil and caused a greater accumulation in plants (Zea mays (corn) and Pisun sativum (pea)) from less than 500 mg•kg −1 to more than 10,000 mg•kg −1 [42].…”
Section: Prospects Of Phytoremediation Of Heavy Metal Contaminated Soilsmentioning
confidence: 99%
“…portulacastrum is a long known medicinal plant traditionally used by healers in South Africa to treat infections (Magwa et al, 2006), where it was used as a remedy for fever, kidney disorders and scurvy (Rojas et al, 1992). Sesuvium species containing secondary metabolites have shown a great potential to substitute some artificial raw materials applied in nutraceuticals, cosmetics and perfumery industries (Lis-Balchin & Deans, 1997; Lokhande et al, 2013). Essential oil extracted from the leaves by hydrodistillation have been found to contain active phytochemicals (mostly terpenoids), which included (in descending order of amount in the essential oil): o-cymene, alpha-and betapinene, trans-caryophyllene, 1,8-cineole (eucalyptol), limonene, alpha-terpinene and alphaterpinolene, camphene, bornylacetate, tridecane and alpha-humulene.…”
Section: Sesuvium Portulacastrummentioning
confidence: 99%